SUPPLY OF SUGAR IN INDONESIA: AN EMPIRICAL STUDY - Riski Ananda Putra; Abdul Hakim (LPPM STIE DHARMAPUTRA SEMARANG, 2013)
This paper analyzes the supply of sugar in Indonesia from the revenue side. The independent variables included in the model are domestic sugar price, import sugar price, tea price, coffe price, and a government policy on the pricing of provenue sugar price. The Error Correction Model (ECM) that is used to help analyzing the data finds that all variables influence the dependent variable both in the long run and in the short run, except the price of coffe.Keywords: Supply of sugar, sugar price, tea, coffe, provenue priceJEL classification numbers: L66, Q18